O trabalho como princípio educativo nas escolas itinerantes do MST no Paraná - Silva , Janaine Zdeski da (2013)
This paper addresses the relationship between work and education with focus on education. Therefore, we take as the object of study work as an educational principle in Schools Itinerant MST in Paraná. Our goal is to understand how they have established the relationship between work and education in Intinerant Schools, considering the role of the school transmission / acquisition of content historically built by humanity, understanding that access to this knowledge is expressed as humanization. Therefore, we performed literature research monographs, dissertations and theses that deal with thematic and documentary analysis of MST’s Bulletins, Notebooks from Itinerant School and yearly reports of the same. Initially, we concentrate on the debate about the working class as an educational principle, indicated as polysemic category interpreted in different ways by authors of educational, who are studied by Brazilian critic. Below are some criticisms that have been built to defend the work as an educational principle, in order to show the debate that this issue has incited. We follow the presentation thinking about the proposed school and the educational experience of Itinerant Schools MST in Paraná. The analysis of documents and academic research on the subject has allowed us to identify the relationship between work and education, that, in different ways, materializes in Schools Itinerant, through work or study time work in the camp, which has enabled enhance the teaching-learning content only sporadically and restricted to a few disciplines, seeking to respond to the immediate needs of the school or camp. It does not indicate that the school has not worked hard enough the content dimension, only that it is not based, mostly, on linking school to work, as the proposal indicates. We identified that the presence of the work in Intinerant Schools binds much more able to contribute to the self-organization of students and the formation of attitudes and values, than intentionalizing teaching-learning contents. The formation of values and attitudes are present in the proposed MST school's and Itinerant School, articulating with the search for the construction of the settlement and the construction of socialism, and are based on relationships and collective practices combined with class perspective that assumes MST .